Legal Protection for Corruption Crime Reporters (Whistle Blower) in Bandung High Court Decision Number: 32/PID.TPK/2022/PT BDG - Muhamad Maulana Yusup (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
Legal protection for reporting witnesses in criminal acts of corruption is part of and protects human rights, because witnesses in corruption cases are considered community participation to reveal criminal acts that are very detrimental to the state, so that the state has an obligation to protect the human rights of its citizens, will However, many people do not want/reluctant to become witnesses, for the reason that there is no clear legal protection, especially for witnesses reporting criminal acts of corruption. The role of someone who reports actions around them, especially within the agency where they work, or what is known as a whistle blower is very important in efforts to eradicate corruption in Indonesia. Therefore, the whistle blowing system must continue to be improved starting from the rules and implementation. The approach method used in this research is normative juridical research, namely analyzing written law, library materials and document studies are used as the main material while field data through interviews is used as supporting/complementary data. Data Analysis, after all secondary data has been obtained through library research, as well as supporting data from interviews, examination and evaluation are carried out to determine its validity, then the data is grouped into similar data. Qualitative data is interpreted juridically, logically, systematically using deductive and inductive methods. Indonesians are still afraid to become whistle blowers, because there are many risks that must be faced, and are even difficult to avoid. Threats of demotion, suspension, even firing, will occur. In fact, reporting someone related to a corruption case to law enforcement officials could also be dangerous for him. Therefore, it is necessary to provide legal protection for whistle blowers so that people are not afraid to become whistle blowers.